Extractive industries, social licensing and corporate social responsibility - Saenz, Cesar (Emerald Publishing Limited, 2024)
Communities are rightly concerned about the indiscriminate use of natural resources, environmental pollution, poverty, health, and education, among other social problems. Extractive and industrial companies therefore face the challenge of not only mitigating their social and environmental impacts, but also contributing proactively to the development of the communities within and beyond their area of influence. The challenge will always be to demonstrate that company operations generate well-being for shareholders and the communities. Extractive Industries, Social Licensing and Corporate Social Responsibility provides analytical tools to allow companies to improve their proposal to mitigate and compensate for their socio-environmental impacts and contribute to the development of the communities, as well as strategies used to improve the conditions of communities within and beyond their area of influence. These strategies can ensure the viability of projects, demonstrating that company operations generate a win-win relationship between companies and their communities. The interdisciplinary focus of the chapters presented here appeals to researchers in the areas of environment, ecology, economics and sociology, and practitioners in the extractive industries.
Keywords: Social responsibility of business.; Mineral industries -- Social aspects.; Mineral industries -- Environmental aspects.; Business & Economics -- Environmental Economics.; Business ethics and social responsibility.; Environmental economics.; elektronické knihy; electronic books